Changes in the Response of Fiscal Policy to Monetary Policy in the EMU - Sanchit Arora; Claire Reicher (Kiel Institute for the World Economy (IfW), 2014)
We study the evolution of the response of fiscal policy to monetary policy shocks in the EMU in the light of two important events: the signing of the Maastricht treaty in 1992 and the introduction of the EMU in 1999. Based on impulse responses from a panel VAR, we find that fiscal and monetary policy acted neutrally toward each other before the Maastricht Treaty; fiscal and monetary policy acted as substitutes immediately after the Maastricht Treaty; and fiscal and monetary policy acted as complements after the introduction of the EMU. These results holds for a set of 11 non-EMU countries as well, which indicates that the evolution of the fiscal response to monetary shocks within the EMU has broadly mirrored global developments. One example of such a global development is the global shift toward lower interest rates and tighter fiscal policy during the 1990s.
Keywords: E52; E62; E65; 330; monetary policy; fiscal policy; panel VAR; Maastricht Treaty; EMU